Physical activity in caregivers: What are the psychological benefits? - Loi, S.; Dow, B.; Ames, D.; Moore, K.; Hill, Keith; Russell, M.; Lautenschlager, N. (Elsevier Ireland Ltd, 2014)
Previous research demonstrates that physical activity has psychological benefits for people of all ages. However, it is unclear whether people caring for a frail or ill relative would derive similar psychological benefits, considering the potentially stressful caregiver role. This article reviews the current literature describing the effect of physical activity interventions on the psychological status of caregivers.A search from January 1975 to December 2012 identified five intervention studies investigating physical activity and psychological status in caregivers. These focused on female Caucasian caregivers who were older than 60 years. The physical activity interventions improved stress, depression and burden in caregivers, but small sample sizes, short-term follow up and varying results limited the generalizability of the findings. There were few trials investigating male caregivers, and most care-recipients were people with dementia.Studies with caregivers of different ages and gender, with a range of physical activity interventions, are needed to clarify whether physical activity has psychological benefits for caregivers.